Inflationary household uncertainty shocks - Gene Ambrocio (Bank of Finland, 2020)
I construct a novel measure of household uncertainty based on survey data for European countries. I show that household uncertainty shocks are not universally like negative demand shocks. Notably, household uncertainty shocks are largely inflationary in Europe. These results lend support to a pricing bias mechanism as an important transmission channel. A comparison of results across countries suggest that demographics and factors related to average markups along with monetary policy play a role in the transmission of household uncertainty to inflation. I develop an Overlapping Generations New Keynesian model with Deep Habits to rationalize these results.
URN:NBN:fi:bof-202004282092; Additional information: A revised version published on 14 Feb 2022 is available as BoF DP 5/2022.; More recent version: http://hdl.handle.net/10419/251465
Keywords: D84; E20; E30; E71; 330; uncertainty; inflation; household expectations; deep habits; demographics